Vanadium, cobalt, zinc, and rubidium are associated with markers of inflammation and oxidative stress in a Greek population with obesity - Amerikanou, Charalampia; Kleftaki, Stamatia-Angeliki; Karavoltsos, Sotirios; Tagkouli, Dimitra; Sakellari, Aikaterini; Valsamidou, Evdokia; Gioxari, Aristea; Kalogeropoulos, Nick; Kaliora, Andriana C. (Frontiers in Endocrinology, 2023)
Introduction The prevalence of obesity is rising globally, with negative effects on the socioeconomic system. As a result of its drivers which include low-grade chronic inflammation, oxidative stress, and fatty acid metabolism, this phenotype develops metabolic anomalies that exacerbate its pathogenesis. It has been discovered that metals and metalloids have substantial effects on both the immune system and metabolism and are influenced by factors connected to obesity. Although there is a known connection between metals, obesity, and related metabolic disorders, it is still under research. Methods We determined the plasma levels of 16 metals and metalloids in 76 individuals with obesity and investigated the relationships with inflammatory and oxidative stress biomarkers in order to clarify the processes by which metals/metalloids exhibit their effects. Results After adjusting for age, gender, BMI, physical activity level, smoking, the existence of metabolic abnormalities, and dietary intake of the corresponding metal, regression analysis revealed the following statistically significant associations; vanadium was negatively associated with oxLDL (Beta ± SE= -0.014 ± 0.005, p=0.007), zinc was negatively associated with leptin (Beta ± SE= -12.390 ± 5.226, p=0.025), cobalt was associated negatively with adiponectin (Beta ± SE= -0.030 ± 0.012, p=0.001) and positively with MPO (Beta ± SE= 0.002 ± 0.001, p=0.023), and rubidium was negatively associated with oxLDL (Beta ± SE= -1.139 ± 0.411, p=0.008) and positively with MPO (Beta ± SE= 0.324 ± 0.102, p=0.003). Discussion The aforementioned associations highlight the need for further research, demonstrating the importance of inflammation and oxidative stress in the association between metals/metalloids and obesity-related metabolic abnormalities.